Tension-type Headache and Migraine as Manifestations of Chronic Post-Traumatic Headache: Case Report - ERIC HARTONO TEDYANTO; I MADE OKA ADNYANA; I PUTU EKA WIDYADHARMA (HANG TUAH MEDICAL JOURNAL, 2023)
Introduction: A subsequent headache that appears within seven days of a head injury is referred to as a post-traumatic headache (PTHA) (or after regaining consciousness after the head trauma). If a post-traumatic headache lasts longer than three months after the injury, it is referred to as chronic or chronic post-traumatic headache (CPTHA). Case Report: A 17-year-old male comes to the neurology outpatient clinic with complaints of headache. The headache has been felt since 3 months ago, 3 days after the patient suffered a blow to his left head from falling from a chair. At that time, the patient fainted about 15 minutes later; the patient regained consciousness and had no complaints. Pain is felt on the left side of the head, throbbing, mild-moderate intensity, and feels heavier when there is a loud sound or seeing a too-bright light. Discussion: Like other primary headaches, post-traumatic headache is diagnosed clinically. Laboratory and routine diagnostic imaging studies are unnecessary and have minimal clinical utility. Brain MRI did not reveal any structural changes in patients with PTHA following injury. Conclusion: Chronic post-traumatic headaches often occur after brain injury, especially after minimally traumatic brain injury. The clinical picture is variable and may be similar to tension-type headaches and/or migraines.